Prioritizing 'equity' in COVID-19 vaccine distribution through Global Health Diplomacy - Bawa Singh; Vijay Kumar Chattu (Tabriz University of Medical Sciences, 2021)
With over 4 million deaths worldwide, the current coronavirus disease 2019 (COVID-19)pandemic is regarded as one of the worst pandemics in history. With its wider devastating consequences, even so-called affluent countries could not provide full coverage for COVID-19vaccines and medications to all of their citizens. Against this backdrop, the main aim of this article is to examine how Global Health Diplomacy (GHD) can play a role in prioritizing vaccine equity in the global health agenda in the fight against COVID-19. The majority of developed countries' healthcare systems have been exposed and have reached a tipping point.After the completion of eighteen months of the pandemic, only five countries were able to produce vaccines for the treatment of COVID-19. This pandemic has divided the world into two blocs: those with vaccines, such as the United States, the United Kingdom, Russia, China, and India; and those without, such as the rest of the world. The greatest challenges are vaccine inequalities, inequities and distribution, which undermine the global economic recovery. Many poor countries are still waiting for the initial doses to be delivered to their citizens, while some rich nations are planning for booster doses. GHD plays a critical role in establishing successful global collaborations, funding mechanisms and ensuring international cooperation through the combined efforts of all stakeholders. Besides, global solidarity is necessary to lessen the wider gaps between the vaccination status of rich and poor nations. Therefore, through GHD, the vaccine gaps and inequities can be addressed to strengthen global health security and accelerate global economic recovery.